2016
DOI: 10.2147/prbm.s94177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress and levels of corticosterone on the development of breast cancer in rats

Abstract: Stress is experienced during cancer, and impairs the immune system’s ability to protect the body. Our aim was to investigate if isolation stress has an impact on the development of tumors in rats, and to measure the size and number of tumors and the levels of corticosterone. Breast cancer was induced in two groups of female rats (N=20) by administration of a single dose of N-methyl-N-nitrosourea 50 mg/kg. Rats in the control group (cancer induction condition) were allowed to remain together in a large cage, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…For example, stressed rats (i.e. isolated) that receive a carcinogenic drug such as N-methyl-N-nitrosurea (NMU) express higher levels of blood corticosterone and 30% more mammary tumors that express more corticosterone receptors (CR) as compared to rats that only receive NMU without being stressed [35]. Our results, however, indicated that males from all the groups expressed similar serum levels of corticosterone in adulthood (see Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, stressed rats (i.e. isolated) that receive a carcinogenic drug such as N-methyl-N-nitrosurea (NMU) express higher levels of blood corticosterone and 30% more mammary tumors that express more corticosterone receptors (CR) as compared to rats that only receive NMU without being stressed [35]. Our results, however, indicated that males from all the groups expressed similar serum levels of corticosterone in adulthood (see Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, we hypothesized that corticosterone baseline serum levels would be higher in those adult males that received LPS during puberty as a consequence of enduring HPA axis activity enhancement. Indeed, other studies have shown that stress in adulthood facilitates the progression of different types of cancer [35][36][37][38]. For example, stressed rats (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados muestran una disminución en los niveles de tensión, ansiedad o estrés percibidos en los pacientes oncológicos tras la aplicación de las técnicas de relajación durante la quimioterapia. Dichos pacientes suelen manifestar entre otros síntomas físicos y psicológicos, tensión, ansiedad o estrés durante la aplicación del tratamiento [16][17][18] y el estrés en particular se ha asociado con el deterioro de la capacidad del sistema inmunológico para defender al cuerpo 19,20 . Un estudio experimental que evaluó los beneficios de la práctica diaria, durante una semana, de imaginación guiada en pacientes con CA de mama, mostró que quienes recibían el entrenamiento en relajación manifestaron una disminución significativa en insomnio, dolor, ansiedad y depresión, en contraste con quienes no recibieron dicho entrenamiento, quienes tenían más síntomas de náuseas, vómito y pérdida de apetito, entre otros 16 .…”
Section: Discussionunclassified
“…Our results show a decrease in the levels of tension, anxiety or stress perceived by cancer patients after the application of relaxation techniques during chemotherapy. These patients usually experience, among other physical and psychological symptoms, tension, anxiety or stress during treatment administration [16][17][18] , and stress in particular has been associated with a deterioration of the immune system capacity to defend the body 19,20 .…”
Section: Discussionmentioning
confidence: 99%